2011
DOI: 10.1108/02634501111138536
|View full text |Cite
|
Sign up to set email alerts
|

Brand names and global positioning

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…have a positive influence in attitudes towards the brand [73]. Thus, studies that investigate those aspects in advergames across cultures could be extremely valuable to the field of interactive marketing and games design across cultures.…”
mentioning
confidence: 99%
“…have a positive influence in attitudes towards the brand [73]. Thus, studies that investigate those aspects in advergames across cultures could be extremely valuable to the field of interactive marketing and games design across cultures.…”
mentioning
confidence: 99%
“…Brands that travel globally also require repositioning (Ranchhod et al, 2011). Names that describe product attributes might encounter lack of acceptance when the brand is repositioned.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Previous studies indicate that different name types (for example, personal names and brand names) may carry positive associations in different social contexts (Duthie 2007;Ranchhod et al 2011). Past research has also shown that an individual's names may have differing meaning potentials (Bruning et al 1998).…”
Section: Positive Associationsmentioning
confidence: 99%
“…Past research has also shown that an individual's names may have differing meaning potentials (Bruning et al 1998). Particular lexical units may be adopted as names when they are believed to carry and communicate certain symbolic meanings that represent an individual's cognitive associations and expectations about themselves (Ranchhod et al 2011).…”
Section: Positive Associationsmentioning
confidence: 99%